PENINGKATAN LITERASI KEUANGAN DAN FINTECH SYARIAH BAGI MAHASISWA - Harry Yulianto; Iryani (Bajang Institute, 2021)
Indonesia has a very large sharia fintech growth potential. However, the challenge faced in improving financial literacy in the community was their knowledge and understanding of sharia fintech was still very limited. Therefore, it was necessary to disseminate sharia fintech information to the public, especially to the millennial generation, such as students in the form of training. The implementation uses the lecture method, as well as discussion. The results of the implementation indicated there was an increase in literacy of financial and sharia fintech for students